Aortic arch in rabbits: Morophological and Histological study - Al-Abdula, Maha Abdul-Hadi Abdul-Rida (The Iraqi Journal of Veterinary Medicine, 2017)
The study aimed to investigate the morphological and histological variations of the aortic arch of local breed rabbits (Oryctylagus conniculus). Nine adult local rabbits were obtained to study the aortic arch (four animals for corrosion cast technique, two injected with colored latex and three for histological study). All the rabbits were euthanized and exsanguinatd, for the cast of the aortic arch they injected by self polymerizing resin via the left ventricle of the heart and the specimens were macerated in (KOH %25) for two weeks and the cast of the aortic arch were prepared. Two main branches were identified from aortic arch (except in one cadaver has three branches). The brachiocephalic trunk firstly and the left subclavian artery, the two common carotid artery (right and left) and the right subclavian artery arising from brachiocephalic trunk, the right and left subclavian arteries gave the same branches (double vertebral arteries, costocervical trunk, cervical profound artery, internal thoracic artery, external thoracic artery, superficial cervical artery and continuous as axillary artery). Histologically the wall of the aortic arch is consist of three layers from internal to external: tunica intima, it’s the thinnest layer (1±0.166) µm, tunica media, it’s the thickest layer (12±0.0149)µm and tunica adventitia, the thickness of this layer is (5±0.166)µm. Tunica intima consisted of single layer of endothelial cells, tunica media consisted of numerous elastic lamina in a circular arrangement and the tunica adventitia was consisted of connective tissue, smooth muscle fibers, collagen fibers, few elastic fibers, fibroblast cells, and mast cells vasavasorum. The aortic arch has a large diameter (98±0.2019)µm and thickness of the wall is (18±0.0282)µm to convey the high blood pressure in aortic arch. In conclusion, there was a variation in the branches of the aortic arch in different species of animals when the results compared with other studies and also, the diameter, thickness of the wall of aortic arch varies from one animal to another.